How Different Information Sources Interact in the Interpretation of Interleaved Discourse: The Case of Two-Step Enumerative Structures - Marianne Vergez-Couret; Laurent Prévot; Myriam Bras (Discours)
Little attention has been devoted to interleaved discourse structures despite the challenges they offer to discourse coherence studies. Interleaved structures occur frequently if several dimensions of discourse coherence (semantic, intentional, textual, etc.) are considered simultaneously on relatively large texts. Two-step enumerative structures, a kind of interleaved structure, are enumerative structures in which the items are further developed in an enumerative fashion. We propose in this paper a treatment of the semantic and textual dimensions of such structures. We also propose some generalizations for the treatment of interleaved structures.